Yang Ching-kuns Pilotstudie (1932/33) über das räumliche System periodischer Märkte in China am Beispiel des Kreises Zouping (Shandong) - Matzat, Wilhelm (ERDKUNDE, 1988)
The ,classical’ study of the rural markets in China is the paper by Skinner, published in 1964/65. It has superseded the pioneer study of Yang Ching-kun on the periodic markets in the county of Zouping, conducted in 1932/33 and published in 1944 in mimeographed form only, with the effect that it is practically unknown among German geographers. Although Yang was not acquainted with Christaller’s central place theory, he nevertheless made similar observations: he identifies a three-level hierarchy of rural markets and the radii and geometrical shapes of their service areas. The lasting value of Yang’s paper lies in the fact that he gives concrete and detailed quantitative information on many aspects, economic and social, of the periodic markets. It is worth noticing that he operationalizes the different hierarchy levels by the number of stands for goods and services on a market day, whereas later studies by other authors enumerate the permanent shops - which are not so relevant as indicators. The figures given for the sellers’ area radii which are about 2 to 3 times that of the service areas, are also unique. Within the county there are 26 markets and it is a pity that Yang only mentions half of them by name. His text is void of a map, which has been produced here.